2015
DOI: 10.20906/cps/cilamce2015-0467
|View full text |Cite
|
Sign up to set email alerts
|

Yield design solutions to bearing capacity of a column-reinforced soil foundation under inclined loading

Abstract: Abstract. Most design procedures devised to evaluating the bearing capacity of columnreinforced foundations have mainly dealt with foundations under vertical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…It is noted that the ultimate bearing capacity depends on the constituents' specific weight through dimensionless parameters k = γ r / γ s and ξ = γ s B / C s . A parametric study investigating the influence of the latter parameter on the ultimate bearing capacity has actually shown that ξ slightly affects the derived kinematic approach upper bound estimates of F + ( δ ).…”
Section: Numerical Resultsmentioning
confidence: 99%
“…It is noted that the ultimate bearing capacity depends on the constituents' specific weight through dimensionless parameters k = γ r / γ s and ξ = γ s B / C s . A parametric study investigating the influence of the latter parameter on the ultimate bearing capacity has actually shown that ξ slightly affects the derived kinematic approach upper bound estimates of F + ( δ ).…”
Section: Numerical Resultsmentioning
confidence: 99%